SAT0126 Mental health benefits associated with reduction in disease activity among rheumatoid arthritis patients: a systematic review of the literature. (15th June 2017) - Strand, V; Rendas-Baum, R; Kosinski, M; Brooks, D; Ganguly, R
Abstract : Background: The association between physical functioning and rheumatoid arthritis (RA) disease activity is well established. In randomized controlled trials (RCTs) of RA treatment, reductions in disease activity result in improved physical functioning. The mental health benefits associated with reductions in disease activity are less well recognized. Objectives: Investigate the association between reductions in RA disease activity and measures of mental health status. Methods: A systematic review of the published literature of RCTs in RA was conducted. The search was limited to those published in the last 10 years that included the Short-Form (SF)-36 Health Survey as an outcome measure. Results: The search strategy yielded 77 articles of which 38 were excluded for the following reasons: not RCT (23); focus exclusively on early RA (9); psychometric evaluation (4); review study (1); and off topic (1). Of the 39 articles reporting mean changes in scores on the SF-36 mental health (MH) and role emotional (RE) domains by treatment group, 3 articles also presented these changes in association with reductions in RA disease activity measures. 1–3 In relation to American College of Rheumatology (ACR) response criteria, small to moderate (0.2–0.5 standard deviation [SD]) effect size changes in RE and MH domain scores were observed among RA patients whose ACR responses ranged from 20–49%. Moderate to large effect sizes (0.5–0.8 SD) were reported in RE and MH domain change scores among ACR50 responders. Similar changes in RE and MH domain scores were reported by patients with reductions in Simplified Disease Activity Index (SDAI) of ≥10 points. Conclusions: The benefits of clinically meaningful reductions in disease activity among RA patients not only include improved physical functioning but also meaningful improvements in overall mental health status. The improvement in mental health is positively associated with reduction in disease activity, with only small to moderate improvements associated with less than ACR50 responses. Additional work is needed to investigate the incremental effects of RA therapies on mental health beyond the effects related to improvements in disease activity. References: Emery P, et al. J Rheumatol. 2006;33(4):681–689. Russell AS, et al. Ann Rheum Dis. 2007;66(2):189–194. Strand V, et al. Health Qual Life Outcomes. 2014;12:31. Disclosure of Interest: V. Strand Consultant for: Abbvie, Amgen, AstraZeneca, BiogenIdec, Boehringer Ingelheim, Celltrion, Crescendo, Genentech/Roche, GSK, Janssen, Lilly, Merck, Novartis, Pfizer, Regeneron, Samsung, Sanofi and UCB, R. Rendas-Baum Employee of: Optum, M. Kosinski Employee of: Optum, D. Brooks Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, R. Ganguly Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline